(untitled) (Tanzania Medical Journal, 2009)
Objective: To assess the awareness, attitude and perceptions on HIV AND AIDS vaccine trials among students at the University of Dar es Salaam, Tanzania Study design: This was a descriptive cross sectional study Setting: University of Dar es Salaam, Tanzania Results: A total of 384 were recruited in the study. Out of these 41.7% reported that HIV vaccine can not prevent the spread of HIV. One hundred and four (26.8%) were of the opinion that an HIV vaccine can cause infection to the person vaccinated. A total of 317 (82.0%) perceived an HIV vaccine as an addition rather than a substitute to other existing preventive measures such as condom use, in the fight against HIV and AIDS. The attitude towards an HIV vaccine trial was positive in 87.5% of the students, but only 19.8% would be willing to participate in a vaccine trial with their current level of information. However, 48.2% would participate if they are better informed. Conclusion: The perception and attitude of University of Dar es Salaam students towards HIV vaccine trials were generally positive. However misconceptions were common. Recommendations: The community should be educated more on HIV vaccine trials, and more socio-behavioral studies need to be done among different social groups on HIV vaccine trials. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 5-8